Toll-like receptor–independent gene induction program activated by mammalian DNA escaped from apoptotic DNA degradation - Okabe, Yasutaka (The Rockefeller University Press, 2005)
Deoxyribonuclease (DNase) II in macrophages cleaves the DNA of engulfed apoptotic cells and of nuclei expelled from erythroid precursor cells. DNase II–deficient mouse embryos accumulate undigested DNA in macrophages, and die in feto because of the activation of the interferon β (IFN β) gene. Here, we found that the F4/80-positive macrophages in DNase II (−/−) fetal liver specifically produce a set of cytokines such as IFNβ, TNFα, and CXCL10. Whereas, IFN-inducible genes (2′5′-oligo(A) synthetase, IRF7, and ISG15) were expressed not only in macrophages but also in other F4/80-negative cells. When DNase II (−/−) macrophages or embryonal fibroblasts engulfed apoptotic cells, they expressed the IFN β and CXCL10 genes. The ablation of Toll-like receptor (TLR) 3 and 9, or their adaptor molecules (MyD88 and TRIF), had no effect on the lethality of the DNase II (−/−) mice. These results indicate that there is a TLR-independent sensing mechanism to activate the innate immunity for the endogenous DNA escaping lysosomal degradation.